El profesor se sorprenderá mucho al ver tu solución correcta😉
log((2/5))*((5/2)-(5/2)*x) = -1
-5*log(5)/2 + 5*log(2)/2 - 5*x*log(2)/2 + 5*x*log(5)/2 = -1
1 - 5*log(5)/2 + 5*log(2)/2 - 5*x*log(2)/2 + 5*x*log(5)/2 = 0
1 - 5*log5/2 + 5*log2/2 - 5*x*log2/2 + 5*x*log5/2 = 0
x = -1 / ((-5*log(5)/2 + 5*log(2)/2 - 5*x*log(2)/2 + 5*x*log(5)/2)/x)
suma
/ 32 \ 2 + log|----| \3125/ ------------- 5*log(2/5)
=
/ 32 \ 2 + log|----| \3125/ ------------- 5*log(2/5)
producto
/ 32 \ 2 + log|----| \3125/ ------------- 5*log(2/5)
=
/ 32 \ 2 + log|----| \3125/ ------------- 5*log(2/5)
(2 + log(32/3125))/(5*log(2/5))
/ 32 \ 2 + log|----| \3125/ x1 = ------------- 5*log(2/5)
x1 = (log(32/3125) + 2)/(5*log(2/5))